Impact of Ninjin’yoeito on frailty and short life in klotho-hypomorphic (kl/kl) mice - Amitani, Haruka; Chiba, Shigeki; Amitani, Marie; Michihara, Seiwa; Takemoto, Risa; Han, Likun; Fujita, Nina; Takahashi, Ryuji; Inui, Akio (Frontiers in Pharmacology, 2022)
With the recent aging of society, the prevention of frailty has become an important issue because people desire both a long and healthy lifespan. Klotho-hypomorphic (kl/kl) mice are known to show phenotypes of premature aging. Ninjin’yoeito (NYT) is a traditional Japanese Kampo medicine used to treat patients with vulnerable constitution, fatigue or physical exhaustion caused by aging and illness. Recent studies have reported the potential efficacy of NYT against frailty. We therefore evaluated the effect of NYT on the gait function, activity, the histopathological status of organs and survival using kl/kl mice as a model of aging-related frailty. Two sets of 28-day-old male kl/kl mice were assigned to the vehicle (non-treated; NT), 3% or 5% NYT dietary groups. One set of groups (NT, n = 18; 3% NYT, n = 11; 5% NYT, n = 11) was subjected to the analysis of free walking, rotarod, and spontaneous activity tests at approximately 58 days old. Thereafter, we measured triceps surae muscles weight and myofiber cross-sectional area (CSA), and quantified its telomere content. In addition, we evaluated bone strength and performed histopathological examinations of organs. Survival was measured in the second set of groups (NT, 3% NYT and 5% NYT group, n = 8 each). In the walking test, several indicators such as gait velocity were improved in the NYT 3% group. Similar results were obtained for the latency to fall in the rotarod test and spontaneous motor activity. Triceps muscle mass, CSA and its telomere content were significantly improved in the NYT 3% group. Bone density, pulmonary alveolus destruction and testicular atrophy were also significantly improved in the NYT 3% group. Survival rate and body weight were both significantly improved in the NYT3% group compared with those in the NT group. Continuous administration of NYT from the early stage of aging improved not only gait performance, but also the survival in the aging-related frailty model. This effect may be associated with the improvements in aging-related organ changes such as muscle atrophy. Intervention with NYT against the progression of frailty may contribute to a longer, healthier life span among the elderly individuals.